Comparison of Standard Electrocardiography and Smartphone-Based Electrocardiography Recorded at Two Different Anatomic Locations in Healthy Meat and Dairy Breed Does - Smith, Joe S.; Ward, Jessica L.; Schneider, Benjamin K.; Smith, Fauna L.; Mueller, Mikaela S.; Heller, Meera C. (Frontiers in Veterinary Science, 2020)
Smartphones present multiple applications for ambulatory practice. One of the newer technologies is smartphone-based electrocardiography (ECG). While this technology has been explored in horses and cattle, it has not yet been evaluated for goats. Fifteen goats of dairy and meat breeds were simultaneously tested with both a standard and smartphone-based ECG from two different anatomic locations (base apex and sternal positions). ECGs were compared for quality score, heart rate, and ECG intervals. Smartphone- based ECGs were feasible to collect in all goats under field settings. Scoring indicated higher quality scores for the standard ECG when compared to the smartphone-based ECG, and differences in quality scores were noted between goats of different body types. Heart rate agreement was noted between measurements taken from smart-phone based and standard devices. ECG intervals calculated for smart-phone based ECGs were clinically similar to standard ECG. While not of the same diagnostic quality as standard ECG recordings, smartphone-based ECGs for goats present an easy to collect recording for caprine practice.